Chemical mechanical polishing composition and method for silicon-based materials
By using colloidal silicon dioxide abrasive particles and polymer compositions in silicon substrate polishing liquid, the particle size and charge distribution are optimized, and the quality problem of traditional silicon single-crystal polishing liquid in the nanoelectronics era is solved, achieving high efficiency and low efficiency Defective silicon substrate surface processing.
Patent Information
- Application Number
- CN202380013137.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-30
- Filing Date
- 2023-07-07
- Publication Date
- 2025-01-10
AI Technical Summary
Traditional silicon single-crystal polishing liquid cannot meet the high requirements for the surface processing quality of silicon single-crystals in the nanoelectronics era, and there are problems of light spot defects, haze and scratches.
Using a chemical mechanical polishing composition comprising colloidal silica abrasive particles, a first polymer and a second polymer, by optimizing the particle size distribution, charge and dispersion of the polymer, combined with a surfactant and a pH adjuster, Form an efficient polishing liquid to improve the surface smoothness and flatness of the silicon substrate.
It significantly reduces light spot defects, haze and scratches, improves the surface flatness and material removal rate of silicon substrates, reduces surface roughness, and meets the high-precision polishing needs in the nanoelectronics era.
Smart Images

Figure CN119301207A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical engineering, and in particular relates to a chemical mechanical polishing composition for silicon-based materials and a chemical mechanical polishing method. Background Art
[0002] Chemical Mechanical Polishing (CMP) is a common process for achieving global planarization in integrated circuit manufacturing or other fields. This process is mainly used to obtain a smooth surface that is both flat and free of scratches and impurities. This process polishes various target substrates through a combination of chemical and mechanical forces, and chemical mechanical polishing (CMP) compositions play a decisive role in this process. These compositions are usually aqueous solutions containing various chemical additives and abrasives that are evenly dispersed. CMP compositions are also called polishing slurries, polishing liquids, or polishing compositions.
[0003] Semiconductor materials, mainly silicon materials, have become the most important basic materials in the electronic information industry and occupy a very important position in daily life and industrial applications. More than 95% of semiconductor devices in the world are made of silicon materials, and 85% of integrated circuits are also made of silicon materials. At present, integrated circuit technology has entered the era of nanoelectronics, so the surface processing quality requirements of silicon single crystal polishing wafers are getting higher and higher, and traditional polishing liquids can no longer meet the requirements of silicon single crystal polishing. Silicon wafers used in electronic devices are obtained from single crystal silicon ingots by the pulling method. Silicon ingots are cut into thin wafers with diamond saws. After the rough polishing (also called grinding) process, the silicon wafers are finely polished with a CMP composition to obtain the desired thickness and flatness. The wafer is polished using a CMPT composition, which usually includes primary polishing, optional secondary polishing and final polishing.
[0004] The working principle of the CMP process is: the rotating silicon wafer is pressed against the rotating polishing pad under a certain pressure to make relative motion, and a smooth and flat surface is obtained by combining the mechanical grinding effect of the abrasive in the polishing liquid and the chemical action of various chemical reagents in the polishing liquid. The traditional silicon wafer CMP system consists of the following three parts: a rotating silicon wafer clamping device, a workbench carrying the polishing pad, and a polishing liquid (slurry) supply system. In the CMP process, chemical action plays a very important role, among which the polishing liquid is particularly important. Therefore, the improvement of the polishing liquid has always been the unchanging research and development direction in the industry. Summary of the invention
[0005] An object of the present invention is to overcome the above-mentioned problems existing in the prior art. Preferably, one embodiment of the present invention provides a chemical mechanical polishing (CMP) composition suitable for final polishing of a silicon-containing substrate such as a silicon wafer, after which the treated silicon-containing substrate has a higher surface smoothness and flatness, thereby obtaining a final polished product. An object of the present invention is to overcome the problems of the prior art. In particular, the object of the present invention is to provide a novel CMP composition, which is suitable for final polishing of a silicon-containing substrate (such as a silicon wafer), which CMP composition exhibits a high material removal rate on the one hand, and on the other hand leads to fewer light point defects, lower haze, and a scratch-free product.
[0006] Preferably, an embodiment of the present invention provides a chemical mechanical polishing composition, comprising an abrasive, a first polymer and a second polymer, wherein the dispersion degrees of the first polymer and the second polymer are both at most 2.3.
[0007] Preferably, the colloidal silica abrasive particles in the composition have a zeta potential of at least -3 mV at pH 9 to 12.
[0008] Preferably, the particle size distribution factor of the silica abrasive is at most 1.8, preferably at most 1.3, more preferably at most 1.0, more preferably at most 0.9, and most preferably at most 0.8, wherein the particle size distribution factor is calculated by the formula (D90-D10) / D50.
[0009] Preferably, the steepness coefficient of the silica abrasive grains is at least 34, preferably at least 48, more preferably at least 56, further preferably at least 67, and most preferably at least 74, and the steepness coefficient is calculated by the formula (D30 / D70)*100.
[0010] Preferably, the colloidal silica abrasive particles have a slope coefficient of at most 17, further preferably at most 15, more preferably at most 14, more preferably at most 13, more preferably at most 12, more preferably at most 11 and most preferably at most 10. Preferably, the glass transition temperature of the first polymer and the second polymer is lower than 160°C, preferably lower than 150°C, more preferably lower than 148°C.
[0011] Preferably, the dispersity of the second polymer is at most 2.3.
[0012] Preferably, the first polymer is hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl methyl cellulose, ethyl hydroxyethyl cellulose, carboxymethyl cellulose, carboxyethyl cellulose, carboxypropyl cellulose, methyl cellulose, ethyl cellulose, propyl cellulose, cellulose acetate, their co-formed products, or a combination thereof; preferably hydroxymethyl cellulose, hydroxyethyl cellulose, or hydroxypropyl cellulose, or a combination thereof.
[0013] Preferably, the second polymer is polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), polyacryloyl morpholine, or a combination thereof.
[0014] Preferably, the surfactant is selected from at least one of polyethylene glycol, polypropylene glycol, poly(ethylene oxide)-b-poly(propylene oxide), polyoxyethylene-polyoxypropylene copolymer, polyoxyethylene alkyl ether, polyoxyethylene dodecyl ether, polyoxyethylene hexyl ether, polyoxyethylene-polyoxyethylene alkylamine; poly((ethylene oxide)-b-(propylene oxide)-b(ethylene oxide)) triblock copolymer or a combination thereof.
[0015] Another object of an embodiment of the present invention is to provide a polishing method for a silicon-containing substrate, wherein the method is implemented using the above composition, and the composition is used in a final polishing step.
[0016] The CMP composition provided by the present invention can improve the polishing effect of silicon-containing substrates. The product obtained after polishing has less haze (a fuzzy structure formed on the surface of a silicon wafer after polishing, which is proportional to the surface roughness), low light point defects (LPD, which refers to the number of residual abrasive particles after polishing and CMP cleaning of the silicon wafer. The residual abrasive particles have a negative effect and may cause defects in the further processing of the silicon wafer), fewer scratches, and lower roughness Ra. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is the DSC graph of HEC in the composition provided in the embodiment of the present invention. DETAILED DESCRIPTION
[0018] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0019] The chemical mechanical polishing composition of the present invention comprises an abrasive, a first polymer and a second polymer surfactant, wherein the abrasive is partially or entirely colloidal silica abrasive particles, and the dispersion degree of the first polymer is at most 2.3, and the dispersion degree is the ratio of the weight average molecular weight to the number average molecular weight of the polymer.
[0020] The CMP composition generally comprises an abrasive dispersed in an aqueous carrier. During the polishing process, the abrasive is used to remove excess material from the surface of the substrate, thereby obtaining a flat and smooth surface. Preferably, the abrasive in the present application comprises at least 98 wt % silicon dioxide, with the remainder being metal oxides. In a particularly preferred embodiment, the abrasive is entirely silicon dioxide particles, which are also referred to as abrasive grains.
[0021] Preferably, the silica particles can be silica prepared by pyrogenic process (pyrogenic silica), colloidal silica or a mixture thereof. Colloidal silica refers to particles prepared by wet process, while pyrogenic silica refers to silica prepared by pyrolysis or flame hydrolysis. Colloidal silica can be obtained by wet process such as precipitation (precipitated silica), polycondensation or similar methods.
[0022] When used, the CMP composition of the present invention may contain at least 0.0005wt% (weight percentage) of abrasive, preferably at least 0.005wt%, more preferably at least 0.01wt%, more preferably at least 0.01wt%0.03wt%, more preferably at least 0.05wt% of abrasive, and the abrasive may be all colloidal silica. In specific use, if the weight percentage of the abrasive particles is too low, the material removal rate during the CMP grinding process will be reduced. If the wt percentage of the abrasive is too high, the particles will form undesirable aggregates, which will cause defects such as scratches on the substrate surface during the CMP grinding process. Therefore, when used, the composition preferably contains at most 10wt%, more preferably at most 5wt%, more preferably at most 2wt%, more preferably at most 1wt%, more preferably at most 0.8wt% of abrasive (the abrasive may be all colloidal silica). In a preferred embodiment, the composition comprises 0.0005wt% to 10wt%, more preferably 0.005wt% to 5wt%, more preferably 0.01wt% to 5wt%, more preferably 0.03wt% to 1wt%, most preferably 0.05wt% to 0.8wt% of colloidal silica abrasive particles.
[0023] The average particle size of the abrasive affects the material removal rate from the substrate surface, and the average particle size is usually expressed as a diameter or diameter-related data. The average particle size can be obtained by dynamic light scattering measurements known to those skilled in the art (for example, using the Malvern Mastersizer S from Malvern Instruments). The curve graph obtained by such measurements provides the cumulative volume percentage of particles of a certain size. The D50 average particle size corresponds to a value where 50% of the particles have a diameter less than this value, also referred to as the median value of the average particle size, or the median diameter. In practical applications, a D50 that is too small will result in a reduced material removal rate. Preferably, the colloidal silica abrasive has a D50 of at least 5 nm, more preferably at least 9 nm, more preferably at least 13 nm, more preferably at least 17 nm, and most preferably at least 20 nm, characterized by dynamic light scattering measurement results. On the other hand, if the D50 is too large, poor haze levels and light point defects (LPDs) will appear on the substrate surface during the CMP process. Preferably, the D50 of the colloidal silica abrasive particles, as characterized by dynamic light scattering measurements, is at most 150 nm, more preferably at most 125 nm, more preferably at most 100 nm, more preferably at most 90 nm, and most preferably at most 80 nm. In a specific embodiment, the D50 of the colloidal silica abrasive particles, as characterized by dynamic light scattering measurements, is in the range of 5 nm to 150 nm, preferably 9 nm to 125 nm, further preferably 13 nm to 100 nm, more preferably 17 nm to 90 nm, and most preferably 20 nm to 80 nm.
[0024] D10 means that its corresponding value is: 10% of the particle size is smaller than this value as a whole. In an embodiment of the present invention, the colloidal silica abrasive has a D10 of at least 1 nm, more preferably at least 3 nm, more preferably at least 6 nm, more preferably at least 8 nm, and most preferably at least 10 nm, characterized by dynamic light scattering measurement results. Abrasives with smaller D10 can increase the particle packing density (reduce the void volume) on the substrate surface during the CMP process, which helps to improve the material removal rate. Therefore, the colloidal silica abrasive has a D10 of at most 70 nm, preferably at most 60 nm, further preferably at most 50 nm, more preferably at most 40 nm, and most preferably at most 30 nm, characterized by dynamic light scattering measurement results. In a preferred embodiment, the colloidal silica abrasive has a D10 of 1 nm to 70 nm, more preferably 3 nm to 60 nm, more preferably 6 nm to 50 nm, more preferably 8 nm to 40 nm, and most preferably 10 nm to 30 nm, characterized by dynamic light scattering measurement results.
[0025] Preferably, D90 refers to the value corresponding to which 90% of the particles as a whole have a size smaller than this value. A higher abrasive D90 can improve the material removal rate during the CMP process. Preferably, the colloidal silica abrasive has a D90 of at least 20 nm, preferably at least 30 nm, more preferably at least 40 nm, more preferably at least 50 nm, and most preferably at least 60 nm, as characterized by dynamic light scattering measurement results. However, if the D90 of the abrasive is too high, more undesirable defects, such as undesirable high haze and light spot defects, will appear during the CMP process. Therefore, in an embodiment of the present invention, the colloidal silica abrasive has a D90 of at most 250 nm, preferably at most 200 nm, further preferably at most 180 nm, more preferably at most 160 nm, and most preferably at most 150 nm, as characterized by dynamic light scattering measurement results. In a preferred embodiment, the colloidal silica abrasive particles have a D90 of 20 nm to 250 nm, preferably 30 nm to 200 nm, further preferably 40 nm to 180 nm, more preferably 50 nm to 160 nm, and most preferably 60 nm to 150 nm, as characterized by dynamic light scattering measurements.
[0026] The width of the particle size distribution can be described by a particle size distribution factor, and a wide particle size distribution indicates that the particle size distribution is less uniform. The particle size distribution factor used in this application refers to the value obtained by the formula (D90-D10) / D50. A wide particle size distribution corresponds to a large particle size distribution factor; while a narrow particle size distribution corresponds to a small particle size distribution factor. D90, D10 and D50 can be obtained by dynamic light scattering as described above. Experiments have shown that excessively large particle size distribution factors can lead to undesirable high haze levels, light point defects and scratches on the substrate surface during the CMP process. A small particle size distribution factor corresponds to less particle aggregation. Preferably, the colloidal silica abrasive has a particle size distribution factor of at most 1.8, preferably at most 1.7, more preferably at most 1.6, more preferably at most 1.5, more preferably at most 1.4, more preferably at most 1.3, more preferably at most 1.2, and most preferably at most 1.1.
[0027] In a preferred embodiment of the present application, the abrasive has a larger steepness coefficient. The steepness coefficient used here refers to the value obtained by the formula (D30 / D70)*100. D30 and D70 can be obtained by dynamic light scattering as described above. The numerical value corresponding to D30 means that 30% of the particles as a whole have a size smaller than this numerical value. D70 means that 70% of the particles as a whole have a size smaller than D70. A wide particle size distribution provides a small steepness coefficient, while a narrow particle size distribution provides a large steepness coefficient. The inventors have found that abrasives with a large steepness coefficient cause fewer defects, lower haze levels and fewer light point defects in the substrate surface during the CMP process. Preferably, the colloidal silica abrasive has a steepness coefficient of at least 61, preferably at least 62, more preferably at least 63, further preferably at least 64, further preferably at least 65, and most preferably at least 66. . However, if the steepness coefficient is too large, the material removal rate during the CMP process will be reduced. Therefore, in the embodiments of the present invention, the colloidal silica abrasive grains have a steepness coefficient of at most 98, preferably at most 97, more preferably at most 96, and most preferably at most 95.
[0028] Preferably, the colloidal silica abrasive particles have a D30 of at least 4 nm, preferably 10 nm, more preferably at least 15 nm, more preferably at least 20, most preferably at least 25 nm, and most preferably 30 nm, as characterized by dynamic light scattering measurements. Preferably, the colloidal silica abrasive particles have a D30 of at most 353 nm, preferably at most 250 nm, more preferably at most 168 nm, more preferably at most 130 nm, further preferably at most 103 nm / and most preferably at most 90 nm, as characterized by dynamic light scattering measurements. Further preferably, the colloidal silica abrasive particles have a D30 of 4 nm to 353 nm, preferably 15 nm to 168 nm, further preferably 25 nm to 90 nm, as characterized by dynamic light scattering measurements.
[0029] Preferably, the colloidal silica abrasive particles have a D70 of at least 16 nm, more preferably at least 30 nm, more preferably at least 43, further preferably at least 45 nm, most preferably at least 50 nm, and most preferably at least 62 nm, as characterized by dynamic light scattering measurements. Preferably, the colloidal silica abrasive particles have a D70 of at most 421 nm, preferably at most 300 nm, more preferably at most 218 nm, further preferably at most 150 nm, further preferably at most 137 nm, and most preferably at most 107 nm, as characterized by dynamic light scattering measurements. On the other hand, the abrasive particles have a D70 of 16 nm to 421 nm, preferably 30 nm to 218 nm, and most preferably 45 nm to 107 nm, as characterized by dynamic light scattering measurements.
[0030] Preferably, the abrasive particles should have a small slope coefficient. The term slope coefficient used in this application refers to the absolute value of the rising slope of the particle size distribution diagram divided by the falling slope. The x-axis represents the volume in the particle size distribution diagram and the y-axis represents the percentage of particles. The term rising slope refers to the slope of the tangent (straight line) drawn from P_D01 to P_max. The term falling slope refers to the slope of the tangent (straight line) drawn from P_max to P_D99. P_D01 refers to the point in the particle size distribution diagram where the particle size is equal to D01. Similar to the above-mentioned D50, D01 means that a total of 1% of the particles are smaller than D01. P_D99 refers to the point in the particle size distribution diagram where the particle size is equal to D99. D99 means that a total of 99% of the particles are smaller than D99. P_max refers to the absolute maximum value of the particle size distribution diagram, that is, the point in the particle size distribution diagram where the corresponding particle size volume percentage is the largest. A smaller slope coefficient can be the result of smaller particles being more widely distributed than larger particles, which can improve particle accumulation during polishing. Smaller slope coefficients generally result in fewer defects, fewer light point defects, and lower substrate surface haze levels. Preferably, the colloidal silica abrasive particles should have a slope coefficient of at most 17, and in a preferred embodiment, have a slope coefficient of at most 15, more preferably at most 14, more preferably at most 13, more preferably at most 12, more preferably at most 11, and most preferably at most 10.
[0031] A smaller slope coefficient can be achieved by improving the dispersibility of the particles and reducing the aggregation and agglomeration of the particles. Specifically, a smaller slope coefficient can be obtained by mechanical methods or chemical methods, such as ultrasonic or grinding treatment to decompose aggregates and agglomerates, or by centrifugation to remove large particles, aggregates and agglomerates; chemical methods include operations such as adding chemical additives, such as adding suitable dispersants. For example, the first polymer and the second polymer of the present invention can interact with the particles and act as dispersants in the composition. The first polymer and the second polymer according to the present invention can help prevent the aggregation and agglomeration of the particles, thereby being used to achieve the desired slope coefficient. Similarly, the above-mentioned mechanical and chemical methods are also applicable to improving the steepness coefficient and particle size distribution factor of the composition of the present application.
[0032] Preferably, the abrasive particles should have a negative charge. The charge refers to the zeta potential, which can be measured, for example, by a Mastersizer S (Malvern Instruments). As known to those skilled in the art, the zeta potential refers to the potential at the interface between the flowing fluid in the composition and the fixed fluid layer attached to the surface of the abrasive particles dispersed in the composition. The zeta potential generally depends on the pH value of the composition. The higher the absolute value of the zeta potential, the stronger the electrostatic repulsion between the particles and the higher the dispersion stability of the particles in the composition. Preferably, the colloidal silica abrasive particles have a zeta potential of at least -5mV, more preferably at least -10mV, more preferably at least -15mV, at least -20mV, and most preferably at least -25mV in the composition. Preferably, the colloidal silica abrasive particles have a zeta potential of at most -70mV, preferably at most -60mV, more preferably at most -55mV, more preferably at most -50mV, and most preferably at most -45mV under conditions of pH 9 to 11. Preferably, the colloidal silica abrasive in the CMP composition of the present application has a zeta potential of -5 mV to -70 mV, more preferably -10 mV to -60 mV, more preferably -15 to -55 mV, more preferably -20 mV to -50 mV, more preferably -25 mV to -45 mV at a pH of 9 to 11.
[0033] Preferably, the composition further comprises one or more chemical additives. The chemical additives may interact with the abrasive and / or with the substrate and / or with the polishing pad during the CMP process. The interactions may be based on hydrogen bonds, van der Waals forces, electrostatic forces, etc. The chemical additives may be any suitable ingredients, such as removal rate accelerators, polishing rate inhibitors, surfactants, thickeners, conditioning agents, complexing agents, chelating agents, preservatives, dispersants, oxidants, film formers, etching inhibitors, catalysts, termination compounds, dissolution inhibitors, or combinations thereof.
[0034] Preferably, the composition further comprises an aqueous carrier in which the abrasive particles and chemical additives are suspended or dissolved. The aqueous carrier enables the abrasive particles and chemical additives to contact the substrate and polishing pad during the CMP process. The aqueous carrier can be any suitable component for suspending the abrasive particles and chemical additives. The aqueous carrier can be water, ethers (e.g., dioxane or tetrahydrofuran), alcohols (e.g., methanol and ethanol), and combinations thereof. Preferably, the aqueous carrier comprises at least 50 wt % of water, preferably at least 70 wt % of water, more preferably at least 90 wt % of water, more preferably at least 95 wt % of water, more preferably at least 99 wt % of water. Most preferably, the aqueous carrier is deionized water.
[0035] Preferably, when used, the CMP composition further comprises a pH regulator. The pH regulator helps to make the composition reach a suitable pH. The pH regulator also acts as an etchant and is used to assist in polishing the silicon-containing substrate. The pH regulator can be a base or a salt thereof, specifically an organic base, an inorganic base or a combination thereof. The organic base can be a quaternary ammonium hydroxide (e.g., tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), tetrapropylammonium hydroxide (TPAH), tetrabutylammonium hydroxide (TBAH)), piperazine, pyrazine, guanidine (e.g., guanidine carbonate, guanidine hydrochloride, arginine, creatine), imidazole, triazole, methylamine, ethylamine, dimethylamine, diethylamine, trimethylamine, triethylamine, ethylenediamine, monoethanolamine, diethanolamine, aminoethylethanolamine, linear primary diamine (e.g., butane-1,4-diamine, pentane-1,5-diamine, hexane-1,6-diamine, heptane-1,7-diamine, octane-1,8-diamine) or a combination thereof. Inorganic bases include alkali metal hydroxides (e.g., potassium hydroxide, sodium hydroxide, lithium hydroxide), alkaline earth metal hydroxides (e.g., magnesium hydroxide, calcium hydroxide, beryllium hydroxide), alkali metal carbonates (e.g., potassium carbonate, potassium bicarbonate, sodium carbonate, sodium bicarbonate, lithium bicarbonate), alkaline earth metal carbonates (e.g., magnesium carbonate, calcium carbonate, beryllium carbonate), alkali metal phosphates (e.g., tripotassium phosphate, trisodium phosphate, dipotassium phosphate, disodium phosphate), alkaline earth metal phosphates (e.g., magnesium phosphate, calcium phosphate, beryllium phosphate), ammonium carbonate, ammonium bicarbonate, ammonium hydroxide, ammonia, or a combination thereof. Preferably, the pH adjuster is an inorganic base. In a particularly preferred embodiment, the pH adjuster is selected from alkali metal hydroxides, alkaline earth metal hydroxides, ammonium hydroxide, ammonium carbonate, ammonia, and a combination thereof. In a particularly preferred embodiment, the pH adjuster is ammonia. Experiments have shown that the pH adjuster of the present application can increase the material removal rate of the silicon-containing substrate.
[0036] Preferably, when used, the composition of the present application comprises at least 0.0001wt%, more preferably at least 0.0005wt%, more preferably at least 0.001wt%, more preferably at least 0.003wt%, more preferably at least 0.005wt% of a pH regulator. Preferably, when used, the composition of the present application comprises at most 2wt%, more preferably at most 1wt%, more preferably at most 0.5wt%, more preferably at most 0.15wt%, more preferably at most 0.09wt% of a pH regulator. In a preferred embodiment, the composition comprises 0.0001wt% to 2wt%, preferably 0.0005wt% to 1wt%, more preferably 0.001wt% to 0.5wt%, more preferably 0.003wt% to 0.15wt%, more preferably 0.005wt% to 0.09wt% of a pH regulator.
[0037] Optionally, the composition of the present invention further comprises a buffer, which may be a phosphate, sulfate, acetate, borate, ammonium salt or a combination thereof. The buffer maintains the composition in a specific pH range, which affects the removal rate of the substrate during the polishing process. And an alkaline pH value can increase the material removal rate of the substrate during the polishing process. Therefore, when used, the composition preferably has a pH of 7.0 or more, preferably 7.5 or more, preferably 8.0 or more, more preferably 8.5 or more, and most preferably 9.0 or more.
[0038] Preferably, the composition of the present application also includes a first polymer. Preferably, the first polymer is a hydrophilic nonionic polymer. Preferably, the first polymer is a water-soluble polymer. As used herein, the term "water-soluble" refers to a polymer having a solubility of at least 0.1 mg / ml in water at 25°C. Preferably, the first polymer is readily soluble in water at 25°C. The first polymer may be a homopolymer, a copolymer, or a combination thereof. Preferably, the first polymer is a homopolymer. Preferably, the first polymer is a cellulose compound. Examples of the first polymer are hydroxymethylcellulose, hydroxyethylcellulose (HEC), hydroxypropylcellulose (HPC), hydroxypropylmethylcellulose (HPMC), hydroxyethylmethylcellulose (HEMC), ethylhydroxyethylcellulose, carboxymethylcellulose, carboxyethylcellulose, carboxypropylcellulose, methylcellulose, ethylcellulose, propylcellulose, cellulose acetate, their co-formed products, or their combinations. In a particularly preferred embodiment, the first polymer is selected from hydroxymethylcellulose, hydroxyethylcellulose (HEC) and hydroxypropylcellulose (HPC) and combinations thereof. The first polymer has the functions of a wetting agent and a thickening agent at the same time.
[0039] Further, the first polymer should have a narrow molecular weight distribution. The wide molecular weight distribution of the polymer may cause undesirable defects on the surface of the substrate. The width of the distribution can be described by dispersity (D). Dispersity refers to the ratio of the weight average molecular weight to the number average molecular weight of the polymer. Dispersity can be measured, for example, by commercially available gel permeation chromatography (Agilent 1260 series, agilent technologies). High dispersity is associated with a wide molecular weight distribution of the polymer, while low dispersity is associated with a narrow molecular weight distribution of the polymer. Preferably, the first polymer has a dispersity (D) of at most 2.30, more preferably at most 2.20, more preferably at most 2.10, more preferably at most 2.00, more preferably at most 1.90, and most preferably at most 1.85. Low dispersity polymers can be achieved by, for example, synthesis and dialysis. Experiments have shown that the first polymer with low dispersity used in the embodiment of the present invention can reduce the number of defects such as scratches and nano scratches in the surface of the silicon-containing substrate during polishing, wherein scratches refer to the damaged area on the surface of the wafer, and nano scratches are relatively shallow, slightly visible under natural light, but usually cover the surface of the entire silicon wafer.
[0040] The first polymer should have a lower glass transition temperature (Tg). The glass transition temperature refers to the temperature at which a material changes from a hard, brittle state to a soft, deformable or rubbery state. The glass transition temperature can be measured using differential scanning calorimetry (DSC), for example, using TA Instruments DSC (Model: SDT Q600, USA). The glass transition can be observed by steps in the baseline, and Tg can be obtained, for example, from half of the step height known to those skilled in the art. The glass transition temperature of a polymer has a great influence on its performance, because the glass transition temperature is related to the mobility of the polymer chain. The more fixed the polymer chain is, the higher the Tg value is. In particular, any structure that restricts rotational motion within the polymer chain will increase the Tg. Due to reduced mobility, bulky, inflexible side groups will increase the Tg of the material. The increase in cross-linking will also reduce the mobility of the polymer, which leads to a reduction in free volume and an increase in Tg. Lower Tg also corresponds to higher flexibility and mobility of the polymer. Preferably, the glass transition temperature of the first polymer is at most 160° C., more preferably at most 158° C., more preferably at most 156° C., more preferably at most 154° C., more preferably 152° C., more preferably 151° C., and most preferably at most 150° C. Experiments have shown that a first polymer with a low Tg can cause the corresponding polymer to have low haze, low LPD, low Ra, fewer scratches and nanoscratches.
[0041] The inventors have also discovered that the ratio of the Tg of the first polymer to the slope coefficient of the colloidal silica particles can be used as a feature of the CMP composition. A high slope coefficient means that the particle size distribution curve has a "tail", which means that there are large particles that may cause defects / scratches. Generally, larger particles are more likely to cause defects than smaller particles. The polymer in the CMP composition can bind to the particles and "cover" them, preventing them from causing scratches. The higher mobility of the polymer (corresponding to a lower Tg) can more effectively bind to the particles and prevent scratches. The inventors found that the higher the ratio of the Tg of the first polymer to the slope coefficient of the colloidal particles, the fewer defects. Preferably, the ratio of the Tg of the first polymer to the slope coefficient of the colloidal abrasive is at least 10, preferably at least 7, more preferably at least 15, more preferably at least 18, further preferably at least 20, further preferably at least 22, and most preferably at least 25.
[0042] Preferably, when used, the CMP composition comprises at least 0.0001 wt%, more preferably at least 0.0005 wt%, more preferably at least 0.001 wt%, more preferably at least 0.002 wt%, more preferably at least 0.004 wt% of the first polymer. Preferably, when used, the composition comprises at most 2 wt%, more preferably at most 1 wt%, more preferably at most 0.5 wt%, more preferably at most 0.15 wt%, more preferably at most 0.1 wt% of the first polymer. In a preferred embodiment, the composition comprises the first polymer in an amount of 0.0001 wt% to 2 wt%, more preferably 0.0005 wt% to 1 wt%, more preferably 0.001 wt% to 1 wt%. 0.5wt%, more preferably 0.002wt% to 0.15wt%, more preferably 0.004wt% to 0.1wt%.
[0043] The first polymer should have a high molecular weight (MW). Molecular weight as used herein refers to weight average molecular weight. Preferably, the molecular weight of the first polymer is at least 10,000 g / mol, more preferably at least 40,000 g / mol, more preferably at least 60,000 g / mol, more preferably at least 80,000 g / mol, and most preferably at least 100,000 g / mol. Preferably, the molecular weight of the first polymer is at most 5,000,000 g / mol, more preferably at most 1,000,000 g / mol, more preferably at most 900,000 g / mol, more preferably at most 800,000 g / mol, and most preferably at most 700,000 g / mol. Preferably, the molecular weight of the first polymer is 10,000 to 5,000,000 g / mol, more preferably 40,000 to 1,000,000 g / mol, more preferably 60,000 to 900,000 g / mol, more preferably 80,000 to 800,000 g / mol, more preferably 100,000 to 700,000 g / mol.
[0044] Preferably, the composition of the present application further comprises a second polymer, preferably, the second polymer is a nonionic polymer. Preferably, the second polymer is a water-soluble polymer. Preferably, the second polymer is easily soluble in water at 25°C. The second polymer may be a homopolymer, a copolymer or a combination thereof. Preferably, the second polymer is a homopolymer. Preferably, the second polymer is a vinyl polymer. The second polymer may be polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), polyacryloylmorpholine. The second polymer can be used to prevent the aggregation of abrasive particles, which may cause defects such as scratches on the surface of the substrate; at the same time, the second polymer can help reduce the swelling of the first polymer.
[0045] Preferably, the second polymer has a dispersion degree (D) of at most 2.30, more preferably at most 2.20, more preferably at most 2.10, more preferably at most 2.00, more preferably at most 1.90, and most preferably at most 1.85. Experiments have shown that the above second polymer makes the polymer of the present application have lower haze, lower light point defects, lower surface roughness, fewer scratches, and fewer nano scratches.
[0046] The inventors have found that the first polymer and the second polymer have low dispersities at the same time, which can make the composition produce the following beneficial effects: low haze, low LPD, and fewer scratches. Preferably, the first polymer and the second polymer have a dispersity (D) of at most 2.30, more preferably at most 2.20, more preferably at most 2.10, more preferably at most 2.00, more preferably at most 1.90, and most preferably at most 1.85.
[0047] Preferably, the glass transition temperature of the second polymer is at most 160° C., more preferably at most 158° C., more preferably at most 156° C., more preferably at most 154° C., more preferably 152° C., more preferably 151° C., and most preferably at most 150° C. Experiments have shown that a second polymer with a low Tg can cause the corresponding polymer to have low haze, low LPD, low Ra, fewer scratches and nanoscratches.
[0048] The inventors have found that the first polymer and the second polymer have low glass transition temperatures at the same time, which can make the composition have lower haze, lower LPD, and fewer scratches. Preferably, the first polymer and the second polymer have glass transition temperatures of at most 160°C, more preferably at most 158°C, more preferably at most 156°C, more preferably at most 154°C, more preferably 152°C, more preferably 151°C, and most preferably at most 150°C.
[0049] The inventors have found that the higher the ratio of the Tg of the second polymer to the slope coefficient of the colloidal particles, the fewer defects. Preferably, the ratio of the Tg of the second polymer to the slope coefficient of the colloidal abrasive particles is at least 5, preferably at least 7, more preferably at least 9, further preferably at least 11, further preferably at least 12, and most preferably at least 13.
[0050] The inventors have found that the higher the ratio of the Tg of the first polymer and the second polymer to the slope coefficient of the colloidal particles, the fewer defects; preferably, the first polymer and the second polymer have a high ratio at the same time. Preferably, the above ratios of the first polymer and the second polymer are at least 5, preferably at least 7, more preferably at least 9, further preferably at least 11, further preferably at least 12, and most preferably at least 13.
[0051] Preferably, when used, the CMP composition comprises at least 0.0001 wt%, more preferably at least 0.0003 wt%, more preferably at least 0.0005 wt%, more preferably at least 0.001 wt%, more preferably at least 0.002 wt% of the second polymer. Preferably, when used, the composition comprises at most 2 wt%, more preferably at most 1 wt%, more preferably at most 0.5 wt%, more preferably at most 0.12 wt%, more preferably at most 0.08 wt% of the second polymer. In a preferred embodiment, the composition contains 0.0001 wt% to 2 wt%, more preferably 0.0003 wt% to 1 wt%, more preferably 0.0005 wt% to 1 wt%, more preferably 0.001 wt% to 0.12 wt%, more preferably 0.002 wt% to 0.08 wt% of the second polymer.
[0052] Preferably, the second polymer should have a lower molecular weight (MW) than the first polymer. Preferably, the second polymer has a molecular weight of at least 1,000 g / mol, more preferably at least 2,000 g / mol, more preferably at least 3,000 g / mol, more preferably at least 4,000 g / mol, and most preferably at least 5,000 g / mol. Preferably, the molecular weight of the second polymer is at most 500,000 g / mol, more preferably at most 400,000 g / mol, more preferably at most 300,000 g / mol, more preferably at most 200,000 g / mol, and most preferably at most 100,000 g / mol. Preferably, the molecular weight of the second polymer is 1,000 to 500,000 g / mol, more preferably 2,000 to 400,000 g / mol, more preferably 3,000 to 300,000 g / mol, more preferably 4,000 to 200,000 g / mol, more preferably 5,000 to 100,000 g / mol.
[0053] Preferably, the composition of the present invention further comprises a chelating agent, which can help bind unwanted metal ions that may be formed during the CMP process and prevent metal ion contamination of the substrate surface. Suitable chelating agents include: dicarboxylic acids, polycarboxylic acids, amino acids, aminocarboxylic acids, aminopolycarboxylic acids, phosphates, polyphosphates, aminophosphonic acids, phosphonocarboxylic acids and combinations thereof. Dicarboxylic acids can specifically be: oxalic acid, malonic acid, succinic acid, maleic acid, phthalic acid, tartaric acid, aspartic acid, glutamic acid and combinations thereof. Polycarboxylic acids can be: citric acid, butanetetracarboxylic acids and combinations thereof. The aminopolycarboxylic acid can be: ethylenediaminetetraacetic acid (EDTA), hydroxyethylethylenediaminetriacetic acid (HEDTA), triethylene glycol diaminetetraacetic acid (EGTA), diethylenetriaminepentaacetic acid (DTPA), diaminohydroxypropanetetraacetic acid (DTPA-OH), triethylenetetraaminehexaacetic acid (TTHA), iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), bisaminophenoxyethanetetraacetic acid (BAPTA), 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (DOTA), nicotinamide, ethylenediaminebishydroxyphenylacetic acid (EDDHA) and combinations thereof. The aminophosphonic acid can specifically be: ethylenediaminetetra(methylenephosphonic acid) (EDTMP), aminotri(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid) (DTPMP) and combinations thereof. In a preferred embodiment, the chelating agent is an aminopolycarboxylic acid. In a particularly preferred embodiment, the chelating agent is selected from EDTA, DTPA-OH, HEDTA, EGTA, DTPA, TTHA, DTPMP, EDTMP and combinations thereof. Experiments have shown that the chelating agent used in the embodiments of the present invention can increase the material removal rate of the substrate during the polishing process.
[0054] Preferably, when used, the composition of the present invention comprises at least 0.5ppm, preferably at least 1ppm, more preferably at least 4ppm, more preferably at least 8ppm, most preferably at least 10ppm of chelating agent. Preferably, the composition comprises at most 1,000ppm, preferably at most 800ppm, more preferably at most 500ppm, more preferably at most 200ppm, and most preferably at most 100ppm of chelating agent. Therefore, the composition comprises 0.5ppm to 1,000ppm, preferably 1ppm to 800ppm, more preferably 4ppm to 500ppm, more preferably 8ppm to 200ppm, and most preferably 10ppm to 100ppm of chelating agent. As used herein, the term "ppm" refers to one millionth by mass.
[0055] Preferably, the composition comprises a surfactant, which can help enhance stability, improve wettability, control light spot defects, and reduce surface roughness and haze. The surfactant can be an anionic surfactant or a nonionic surfactant. Preferably, the surfactant is a nonionic surfactant. Examples of surfactants are polyethylene glycol, polypropylene glycol, polyglycerol, polyoxyethylene, polyoxypropylene, polyoxybutylene, polyoxyethylene polyoxypropylene glycol, polyoxyethylene polyoxybutylene glycol, polyoxyethylene alkyl ether, polyoxyethylene alkylphenyl ether, polyoxyethylene alkylamine, polyoxyethylene fatty acid ester, polyoxyethylene glyceryl ether fatty acid ester, polyoxyethylene sorbitan fatty acid ester, polyoxyethylene polyoxypropylene copolymer, poly(ethylene oxide)-b-poly(propylene oxide), polyoxyethylene glycol, polyoxyethylene propyl ether, polyoxyethylene butyl ether, polyoxyethylene pentyl ether, polyoxyethylene hexyl ether, polyoxyethylene octyl ether, polyoxyethylene-2-ethylhexyl ether, polyoxyethylene nonyl ether, polyoxyethylene decyl ether, polyoxyethylene isodecyl ether, polyoxyethylene dodecyl ether, polyoxyethylene tridecyl ether, polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, polyoxyethylene isostearyl ether, polyoxyethylene alkenyl ether, polyoxyethylene Ethylene oxide phenyl ether, polyoxyethylene octyl phenyl ether, polyoxyethylene nonyl phenyl ether, polyoxyethylene dodecyl phenyl ether, polyoxyethylene styrene phenyl ether, polyoxyethylene lauryl amine, polyoxyethylene stearylamine, polyoxyethylene oleylamine, polyoxyethylene stearamide, polyoxyethylene oleamide, polyoxyethylene monolaurate, polyoxyethylene monostearate, polyoxyethylene distearate polyoxyethylene monooleate, polyoxyethylene dioleate, polyoxyethylene sorbitan monolaurate , polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan trioleate, polyoxyethylene sorbitol tetraoleate, polyoxyethylene castor oil, polyoxyethylene hydrogenated castor oil, acetylene glycol, polyoxyethylene-polyoxyethylene alkylamine; poly((ethylene oxide)-b-(propylene oxide)-b(ethylene oxide)) triblock copolymer or a combination thereof. Preferably, the surfactant is selected from at least one of polyethylene glycol, polypropylene glycol, poly(ethylene oxide)-b-poly(propylene oxide), polyoxyethylene-polyoxyethylene alkylamine, poly((ethylene oxide)-b-(propylene oxide)-b(ethylene oxide)) triblock copolymer, polyoxyethylene-polyoxypropylene copolymer and polyoxyethylene alkyl ether (PEOLE-polyoxyethylene lauryl ether; or PEOHE-polyoxyethylene hexyl ether). Surfactants are effective in reducing haze levels and light point defects on silicon-containing substrates.
[0056] Preferably, the composition of the present application comprises at least 1 ppm, preferably at least 5 ppm, more preferably at least 10 ppm, more preferably at least 15 ppm, most preferably at least 20 ppm of surfactant. Preferably, the composition comprises at most 5,000 ppm, more preferably at most 3,000 ppm, more preferably at most 1,000 ppm, more preferably at most 800 ppm, and most preferably at most 600 ppm of surfactant. Preferably, the composition comprises the surfactant in an amount of 1 ppm to 5,000 ppm, more preferably 5 ppm to 3,000 ppm, more preferably 10 ppm to 1,000 ppm, more preferably 15 ppm to 800 ppm, and most preferably 20 ppm to 600 ppm.
[0057] Preferably, the surfactant has a molecular weight of at least 100 g / mol, more preferably at least 400 g / mol, more preferably at least 600 g / mol, more preferably at least 900 g / mol, and most preferably at least 1,000 g / mol. Preferably, the molecular weight of the surfactant is at most 50,000 g / mol, more preferably at most 40,000 g / mol, more preferably at most 30,000 g / mol, more preferably at most 20,000 g / mol, and most preferably at most 15,000 g / mol. Preferably, the molecular weight of the surfactant is 100 g / mol to 50,000 g / mol, more preferably 400 g / mol to 40,000 g / mol, more preferably 600 g / mol to 30,000 g / mol, more preferably 900 g / mol to 20,000 g / mol, more preferably 1,000 g / mol to 15,000 g / mol.
[0058] Preferably, the composition of the present application comprises a surfactant having a dispersity (D) of no more than 2.3, preferably no more than 2.20, more preferably no more than 2.10, more preferably no more than 2.00, more preferably no more than 1.90, and most preferably no more than 1.85. Surfactants having such a dispersity (D) can reduce the number of defects such as scratches and nanoscratches in the surface of silicon-containing substrates during CMP polishing, and can also reduce haze, LPD, and surface roughness.
[0059] The inventors have found that the first polymer, the second polymer and the surfactant all have low dispersities, which can make the above composition have low haze, low LPD, fewer scratches, and fewer nanoscratches. Further preferably, the first polymer, the second polymer and the surfactant all have a dispersity of at most 2.30, more preferably at most 2.20, more preferably at most 2.10, more preferably at most 2.00, more preferably at most 1.90, and most preferably at most 1.85.
[0060] The composition of the present application also preferably comprises an acidulant, which can be an organic acid or an inorganic acid. The acidulant can be present in the composition in any suitable form, such as acid, conjugate acid, salt (such as potassium salt, sodium salt, ammonium salt) or its combination. The example of an inorganic acid is hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid, boric acid, carbonic acid, hypophosphorous acid, phosphorous acid, phosphoric acid and a combination thereof. Examples of organic acids are formic acid, acetic acid, propionic acid, butyric acid, valeric acid, methylbutyric acid, caproic acid, dimethylbutyric acid, ethylbutyric acid, methylvaleric acid, enanthic acid, methylhexanoic acid, caprylic acid, ethylhexanoic acid, benzoic acid, glycolic acid, salicylic acid, glyceric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, maleic acid, malic acid, phthalic acid, tartaric acid, muconic acid, citric acid, lactic acid, diglycolic acid, furancarboxylic acid, suberic acid, azelaic acid, aspartic acid, tetrahydrofuranic acid, methoxyacetic acid, methoxyphenylacetic acid, sebacic acid, glutaconic acid, phenoxyacetic acid, methanesulfonic acid, methoxyphenylacetic acid, ethanesulfonic acid, sulfosuccinic acid, benzenesulfonic acid, toluenesulfonic acid, phenylphosphonic acid, hydroxyethyl diphosphonic acid and combinations thereof. Preferably, the acid agent is an inorganic acid. In particularly preferred embodiments, the acid agent is selected from nitric acid, hypophosphorous acid, phosphorous acid, phosphoric acid, sulfuric acid and combinations thereof. The acidic agent in the composition of the present application can adjust the pH value of the composition and increase the wettability of the surface of the polishing substrate.
[0061] Preferably, the composition comprises at least 0.5ppm, preferably at least 1ppm, more preferably at least 4ppm, more preferably at least 8ppm, most preferably at least 10ppm of the above-mentioned acid agent. Preferably, the composition comprises at most 1,000ppm, more preferably at most 800ppm, more preferably at most 500ppm, more preferably at most 200ppm, and most preferably at most 100ppm of the above-mentioned acid agent. Preferably, the composition comprises 0.5ppm to 1,000ppm, more preferably 1ppm to 800ppm, more preferably 4ppm to 500ppm, more preferably 8ppm to 200ppm, and most preferably 10ppm to 100ppm of the acid agent.
[0062] Optionally, the composition also includes one or more preservatives. Preservatives can be any suitable compound, which can prevent, inhibit, reduce the growth of unwanted microorganisms, inhibit its activity or eliminate unwanted microorganisms. The example of suitable preservatives is sodium hypochlorite, methylisothiazolinone, benzisothiazolinone, chloromethylisothiazolinone and combination thereof. Preferably, when in use, the composition includes at least 0.1ppm by weight, more preferably at least 1ppm by weight, more preferably at least 1.5ppm, more preferably at least 2ppm, most preferably at least 2.5ppm preservative. High concentrations of preservatives can cause undesirable interactions between preservatives and other components of the composition and substrates. Therefore, when in use, the composition preferably includes at most 100ppm by weight, more preferably at most 80ppm, more preferably at most 75ppm, more preferably at most 70ppm preservative.
[0063] Another aspect of the present invention provides a method for chemical mechanical polishing of a silicon-containing substrate, the method comprising the following steps: (a) providing the chemical mechanical polishing composition described above; (b) contacting the silicon-containing substrate with the chemical mechanical polishing composition and a polishing pad; (c) moving the polishing pad relative to the silicon-containing substrate, with the chemical mechanical polishing composition located therebetween; and (d) removing at least a portion of the silicon-containing substrate. The method may optionally include other steps.
[0064] The abrasive particles of the present application and the above-mentioned features of the abrasive particles can be obtained by methods well known to those skilled in the art. In a specific embodiment, the colloidal silica particles can be prepared by polycondensation, for example, by condensing Si(OH)4 to form spherical particles. Si(OH)4 can be obtained by hydrolysis of alkoxysilanes or acidification of silicate aqueous solutions. The colloidal silica abrasive particles can be prepared by precipitation from an acidic solution containing sodium silicate and sulfuric acid. Colloidal silica abrasive particles can also be purchased from the market, such as Bayer, DuPont, Fuso Chemical Company, Nalco and Nissan Chemical. The particles are dispersed, for example, by stirring and used to formulate the composition.
[0065] Regarding the above-mentioned abrasives and chemical additives, they can be added to the aqueous carrier in any order in appropriate amounts to achieve the desired concentration, thereby preparing the composition. The abrasive particles and chemical additives can be mixed and stirred in the aqueous carrier. The pH can be adjusted using the above-mentioned pH adjusters and pH buffers to obtain and maintain the desired pH. The abrasive particles and chemical additives can be added before use or at any time during the CMP process (e.g., one month, one day, one hour, or one minute).
[0066] The above composition can be provided as a one-part system, a two-part system, or a multi-part system. For example, as a two-part system, the first part can contain abrasive particles and one or more chemical additives, and the second part can contain a pH adjuster and one or more chemical additives. The first part and the second part can be combined at any time (e.g., one month, one day, one hour, or one minute) before or during the CMP process, such as when using a polishing device with multiple supply paths for the CMP composition.
[0067] The above composition may be provided as a concentrate and may be diluted with an appropriate amount of water prior to use. The concentrations of the composition components may be any suitable, for example 2, 3, 10, 25 or 100 times the above point of use concentrations. For example, the concentrate contains abrasive particles and chemical additives in concentrations such that upon dilution with an appropriate amount of water, the abrasive particles and optional chemical additives are present in the composition at the concentrations as described above. If the composition is provided, for example, as a two-part system, one or both parts may be provided as a concentrate. The two parts may be provided at different concentrations, for example the first part may be three times concentrated and the second part may be five times concentrated. The two parts may be diluted in any order prior to mixing.
[0068] The present invention also relates to the use of the above-mentioned composition of the present invention. Preferably, the composition of the present invention is used for chemical mechanical polishing of silicon-containing substrates. The composition can be used for surface polishing of silicon wafers, such as for polishing in primary polishing, secondary polishing, final polishing and silicon wafer recycling. In a preferred embodiment, the composition according to the present invention is used for final polishing of silicon wafers. Preferably, silicon can be undoped silicon or doped silicon, such as boron or aluminum doped silicon. Silicon can also be single crystal silicon or polycrystalline silicon. In a specific embodiment, silicon can also include silicon oxide. As known to those skilled in the art, chemical mechanical polishing refers to: in a CMP device, a substrate is arranged to contact with a polishing pad and a CMP composition located therebetween, and the polishing pad moves relative to the substrate to remove part of the substrate, preferably, the substrate is undoped single crystal silicon.
[0069] The present application is described in detail below through specific embodiments.
[0070] Example 1 Preparation of Low Dispersity Polymers The dispersity of all three polymers can be controlled by the temperature, time and ratio of added molecules during the synthesis process, which is known to those skilled in the art.
[0071] Synthesis of Hydroxyethyl Cellulose (HEC):
[0072] 7.5 g of NaOH, 11 g of urea and 81.5 g of distilled water were added to a beaker, the resulting solution was precooled at -12 ° C, and then 200 g of cellulose was added and vigorously stirred at room temperature for 10 minutes. A mixture of anhydroglucose units (AGU) and chlorohydrin in a 1:6 molar ratio was added to the above cellulose solution, stirred at room temperature for 1 hour, and heated to 50 ° C for 5 hours. The resulting crude polymer was neutralized with acetic acid, then dialyzed and freeze-dried, and the resulting HEC polymer had a dispersity of 1.51.
[0073] Synthesis of polyvinylpyrrolidone (PVP) (the preparation steps can refer to US 6,486,281 B1)
[0074] 120 g of vinyl pyrrolidone, 180 g of water, 6.6 g of ammonium sulfite (5.5% based on the weight of vinyl pyrrolidone) and 0.96 g of tert-butyl hydroperoxide (0.8% based on the weight of vinyl pyrrolidone) were added to 25 g of the regenerated anion exchange resin and stirred at 50° C. for 1 hour to disperse. The VP polymer (PVP) aqueous solution and the anion exchange resin were then separated from each other by centrifugation, and the obtained PVP dispersion degree was 1.62.
[0075] In other embodiments, PVP may be synthesized by free radical polymerization using azobisisobutyronitrile (AIBN) as an initiator.
[0076] Synthesis of PEO-b-PPO
[0077] PEO-b-PPO was prepared by anionic polymerization using potassium tert-butoxide as initiator.
[0078] To synthesize the diblock copolymer with tert-butyl end groups on PPO, the PPO block was first synthesized by initiating and propagating propylene oxide using potassium tert-butoxide as an initiator at room temperature. 18-Crown-6 ether was added to the reaction at a molar ratio of 2:1 to the initiator to reduce the dispersity and increase the conversion of propylene oxide. After 48 hours, the reaction was terminated with acidic methanol (37w / w% hydrochloric acid: methanol ratio of 1:10). The potassium and crown ether complexes were removed by filtration, solvent removal, and dissolution in fresh THF until a clear solution was obtained. The PEO block was propagated by reinitiating the PPO block with potassium naphthide at 40°C. The reaction was terminated with acidic methanol after 20 hours. After termination, the diblock copolymer was repeatedly dissolved in fresh solvent and filtered, and then further purified by dialysis. The dispersity of the resulting polymer was 1.15.
[0079] Example 2 Preparation of the composition
[0080] All compositions of the examples were prepared by adding the chemical additives and dissolving them in deionized water, then adding the colloidal silica abrasive and stirring until the colloidal silica abrasive particles were dispersed.
[0081] Example 3
[0082] Compositions A1-A3 and E1-E9 were evaluated for the presence of light spot defects, haze, surface roughness, and scratches on polished silicon wafers. All ingredients contained 0.18wt.% colloidal silica, 0.0015wt.% ethylenediaminetetraacetic acid, 0.0004wt.% nitric acid, 80ppm HEC (MW 500,000g / mol), 40ppm PVP (MW 24,000g / mol), 30ppm PEO-b-PPO (MW 8,400g / mol), and 30ppm preservative KATHONTM LX 150 (Dow Co., Ltd.). The pH value of all ingredients was adjusted to 10.5 with ammonia. Before the components were added to the composition using an Agilent 1260 Infinity II size exclusion chromatography system (Agilent Technologies), the dispersities of HEC, PVP, and PEO-b-PPO were measured and listed in Table 1.
[0083] All compositions were used to polish the silicon wafers, and then the silicon wafers were cleaned as described in the examples. The light point defects of the silicon wafers were measured to be at least 45 nm. In addition, the haze level of the silicon wafers was measured under the same conditions as the light point defects. The light point defects and haze levels relative to composition A2 are listed in percentage in Table 1.
[0084] The polished and cleaned silicon wafer surface was checked for scratches and microcracks. If the silicon wafer was detected to be covered with continuous nano- and microcracks by the measured haze map, the presence of microcracks was considered positive. In addition, the number of non-continuous scratches that could be counted and visible to the naked eye is listed in Table 1.
[0085] A Park AFM instrument was used to measure the size of the wafer within 10 μm of the center. 2 The surface roughness (Ra) of the polished and cleaned silicon wafers was measured at an area of 100 nm and two randomly selected measurement points 3 nm from the edge of the silicon wafer. The surface roughness (Ra) refers to the arithmetic mean of the absolute value of the profile height deviation from the average height. The surface roughness (Ra) is listed in units as the average of two measurement points at the center and near the edge.
[0086] Table 1
[0087]
[0088] As can be seen from Table 1, compositions A1-A3 containing all three polymers HEC, PVP and PEO-b-PPO with higher dispersities exhibited higher haze levels, higher light point defects, microcracks, higher number of scratches and higher surface roughness compared to compositions E1-E9. Examples E1-E3 containing HEC with higher dispersities and PVP and PEO-b-PPO with lower dispersities and Examples E4-E6 containing HEC with lower dispersities and PVP and PEO-co-PPSO with higher dispersities showed no microcracks, one scratch, and significantly lower light point defects, significantly lower haze and significantly lower surface roughness compared to compositions A1-A3. Compositions E7-E9 containing all three polymers HEC, PVP and PEO-b-PPO had lower dispersities, no microcracks, no scratches, and significantly lower light point defects, significantly lower haze and significantly lower surface roughness, etc. Compared to compositions A1-A3 and E1-E6, compositions E7-E9 containing all three polymers HEC, PVP and PEO-b-PPO had lower dispersities, no microcracks, no scratches, and significantly lower light point defects, significantly lower haze and significantly lower surface roughness, etc. Example 4
[0089] The experimental conditions are similar to those of Example 3 (except that the polymer used is a different molecule, as shown in Table 2 below).
[0090] Table 2
[0091] abbreviation:
[0092] HPC-hydroxypropyl cellulose, HEMC-hydroxyethyl methyl cellulose, HPMC-hydroxypropyl methyl cellulose, EHEC-ethyl hydroxyethyl cellulose, PVA-polyvinyl alcohol, PVC-polyethylene caprolactam, PACMO-polyacryloyl morpholine, PVSA-polyethylene sulfonic acid; PEOLE-polyoxyethylene dodecyl ether; PEOHE-polyoxyethylene hexyl ether; PEOAA-polyoxyethylene-polyoxyethylene alkylamine; PEO-b-PPO-b-PEO poly((ethylene oxide)-b-(propylene oxide)-b(ethylene oxide)) triblock copolymer.
[0093] As can be seen from Table 2, compared with compositions A4-A7, Examples E10-E13 containing a first polymer with lower dispersion, a second polymer and a surfactant show no scratches, no nanoscratches, and significantly lower light point defects, significantly lower haze and significantly lower surface roughness.
[0094] Example 5
[0095] Compositions A8-A13 and E14-E17 were evaluated for haze, light spot defects, surface roughness, and scratches on polished silicon wafers. All ingredients included 0.2 wt.% colloidal silica, 0.0012 wt.% ethylenediaminetetraacetic acid, 0.0004 wt.% nitric acid, 0.009 wt.% HEC (MW 250,000 g / mol), 0.006 wt.% PVP (MW 9,6000 g / mol), 0.0025 wt.% PEO-PPO (MW 2,100 g / mol), and 30 ppm preservative KATHONTMLX 150 (Dow Co., Ltd.) (by weight). All ingredients were adjusted to a pH of 10.5 with ammonia. The particle size distribution of the colloidal silica was measured by dynamic light scattering of a Malvern Mastersizer S (Malvern Instruments). D50, particle size distribution factor, slope coefficient and steepness coefficient were obtained as described above and are listed in Table 3. The composition was used to polish the silicon wafer described in Example 3, and then the silicon wafer was cleaned as described in Example 3. Haze, light point defects, surface roughness, scratches and microcracks were measured and evaluated as described in Example 3 and are listed in Table 3.
[0096] Table 3
[0097] It can be seen from Table 3 above that a low particle size distribution factor, a high steepness coefficient and a small slope coefficient have better effects, such as obtaining low light point defects, haze, surface roughness, etc.
[0098] Embodiment 6:
[0099] Hydroxyethylcellulose (HEC) with different glass transition temperatures in A14-A18 and E18-E21 were evaluated to analyze the effect of HEC with different glass transition temperatures on the composition. All compositions contained 0.2 wt% colloidal silica, 0.0012 wt% ethylenediaminetetraacetic acid, 0.0004 wt% nitric acid, 0.009 wt% HEC (MW 250,000 g / mol) (each with a different glass transition temperature as listed in Table 4), 0.006 wt% PVP (MW 8,000 g / mol), 0.0025 wt% PEO-b-PPO (MW 5,800 g / mol), and 30 ppm (by weight) of the preservative KATHON™ LX 150 (Dow Corporation). The pH of all ingredients was adjusted to 10.5 with ammonia. The composition was used to polish the silicon wafer described in Example 3, and then the silicon wafer was cleaned as described in Example 3.
[0100] The glass transition temperature of HEC of all compositions was obtained by differential scanning calorimetry (DSC), and DSC of different HECs was examined on dried powders using TA Instruments DSC (Model: SDT Q600, USA). The heating rate was fixed at 5°C / min under N2 atmosphere.
[0101] The slope coefficient was measured and obtained as described above.
[0102] Table 4
[0103] Examples E18-E21 have lower glass transition temperatures, and the results show that they have the best polishing effect.
[0104] Figure 1 Table shows the results of differential scanning calorimetry for HEC from compositions A17, A18, and E18 heated at a constant rate of 5°C / min. The X-axis represents temperature in °C and the Y-axis represents heat flow divided by the sample weight in the indicated inward direction.
[0105] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A chemical mechanical polishing composition comprising an abrasive, a first polymer and a second polymer, wherein the dispersion degrees of the first polymer and the second polymer are both at most 2.3, and the glass transition temperature of the first polymer is lower than 160°C.
2. The composition according to claim 1, characterized in that Also included is a surfactant, wherein the surfactant has a dispersity of at most 2.
3.
3. The composition according to claim 1, characterized in that The second polymer has a glass transition temperature below 160°C.
4. The composition according to any one of claims 1 to 3, characterized in that The abrasive material is colloidal abrasive particles, wherein the ratio of the glass transition temperature of the first polymer to the slope coefficient of the colloidal abrasive particles is at least 10.
5. A colloidal silica abrasive for use in the chemical mechanical polishing composition according to any one of claims 1 to 4.
6. The colloidal silica abrasive according to claim 5, characterized in that: The colloidal silica abrasive has a slope coefficient of at most 17.
7. The colloidal silica abrasive according to claim 5, characterized in that: The colloidal silica abrasive has a steepness coefficient of at least 34.
8. The colloidal silica abrasive according to claim 5, characterized in that The colloidal silica abrasive has a particle size distribution factor of at most 1.
8.
9. The colloidal silica abrasive according to claim 5, characterized in that: The colloidal silica abrasive has a zeta potential of at least -3 mV at pH 9 to 12.
10. A polishing method for a silicon-containing substrate, the method being implemented using the composition according to any one of claims 1 to 4, and the composition being used in a final polishing step.
Citation Information
Patent Citations
Process for preparing high-purity vinylpyrrolidone polymer
US6486281B1